ASTAXANTHIN MENGHAMBAT PENURUNAN JUMLAH SEL LEYDIG DAN KADAR TESTOSTERON PADA TIKUS WISTAR JANTAN YANG DIPAPAR DENGAN ASAP ROKOK - Andrew Lie; Wimpie Pangkahila; L.P. Iin Indrayani Maker (Perhimpunan Dokter Gizi Klinik Indonesia, 2020)
Background. The exposure of cigarette smoke impacts negatively on Leydig cell count and testosterone level. Astaxanthin is known for its ability to neutralize free radicals far more potent than any other kind of antioxidant. Research objectives. This research aims to prove the effect of Astaxanthin in inhibiting decrease of Leydig cell count and testosterone level in male Wistar rats exposed with cigarette smoke. Methodology. The posttest only control group study design was conducted on 36 male Wistar rats, 12-16 weeks in age, with 200-210 grams body weight. Samples were randomly divided into two groups, consisting of a control group exposed with cigarette smoke and 0.5 ml of aquadest and a study group exposed with cigarette smoke and 0.1 mg of astaxanthin/200 gr BW daily for 30 days. On day 31, blood samples were taken to measure the testosterone level. Both testes were taken for Leydig cells count assessment. Comparative analysis was done to see any significant difference between the study and control group. Research results. The results show that the mean number of Leydig cells and testosterone levels in the study group was significantly higher than the control group (p<0.01). Conclusion. Oral astaxanthin administration inhibited the decrease of Leydig cell count and testosterone level in male Wistar rats exposed with cigarette smoke. Key words: Astaxanthin, Testosterone, Leydig Cell, Andropause